Characterisation of functionally graded and VC/steel surface alloyed composites produced using powder metallurgy - Eroglu, M.; Guler, S. H. (Maney Publishing, 2010)
In this study, low carbon steel specimens with surface alloyed composites were produced by means of powder metallurgy. Vanadium carbide, graphite (1.2 wt-%) and Fe were used for the surface alloyed composite, while Fe and graphite (0.2 wt-%) were used for the low carbon steel side. The powder mixtures were compacted together in the same mould. On the surface alloyed side the vanadium carbide content was changed from 5 to 25 wt-%. Microstructural investigations including EDX and X-ray, hardness measurement and abrasive wear tests were performed. The results showed that V(8)C(7) formed in the alloyed surface and carbon diffusion from the alloyed surface to the parent metal created a functionally graded material. The hardness values decreased towards the parent metal. Wear resistance increased as the vanadium carbide increased in the surface alloyed composite. Thus, a functionally graded steel having a surface composite that is resistant to abrasive wear can be obtained via the powder metallurgy route.
Keywords: Powder metallurgy; VC; Functionally graded material; Steel composite; Microstructure